2012
DOI: 10.4067/s0717-95022012000300005
|View full text |Cite
|
Sign up to set email alerts
|

Skinfold Sum: Reference Values for Top Athletes

Abstract: SUMMARY:Skinfold determinations from different body parts are occasionally used in prediction equations to calculate fatness. This is a critical parameter that conditions optimal sport performance. Reference values of skinfolds in top athletes do not exist. Therefore, the main objective of this study is to present skinfold reference values from a large population of athletes. Triceps, subscapu lar, suprailiac, abdominal, thigh and medial calf skinfolds were measured according to ISAK (International Society for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
20
2
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 8 publications
6
20
2
9
Order By: Relevance
“…It is likely that their maturity has not yet finished and will continue after the age of twenty (Tanner, 1962). Also, the present study showed quite similar results regarding body fat percentage and fat free mass for the guard and forwards and some higher values for the centers (Ostojic et al;Sallet et al;Ben Abdelkrim et al, 2010;Garrido-Chamorro et al, 2012). This small discrepancy in adiposity tissue can be explained by the smaller number of games played, smaller training volumes and the intensity of this research compared to players involved in recent studies, who competed internationally, at higher levels, with their clubs.…”
Section: Pojskic H; Separovic V; Muratovic M and Uzicanin Esupporting
confidence: 83%
“…It is likely that their maturity has not yet finished and will continue after the age of twenty (Tanner, 1962). Also, the present study showed quite similar results regarding body fat percentage and fat free mass for the guard and forwards and some higher values for the centers (Ostojic et al;Sallet et al;Ben Abdelkrim et al, 2010;Garrido-Chamorro et al, 2012). This small discrepancy in adiposity tissue can be explained by the smaller number of games played, smaller training volumes and the intensity of this research compared to players involved in recent studies, who competed internationally, at higher levels, with their clubs.…”
Section: Pojskic H; Separovic V; Muratovic M and Uzicanin Esupporting
confidence: 83%
“…The differences between the two sexes can be explained, on the one hand, by the differences of expansion of the trunk skin folds, while on the other hand, the opposing changes of limb skin folds in the two sexes (Bodzsár). Regular sport activity can also influence this rate, thickness of skin folds depends on the type of the sport (Garrido-Chamorro et al, 2012;Popovic et al, 2013). The significant differences between the age groups in the case of thigh and triceps skin folds further support the authors' hypothesis.…”
Section: Discussionsupporting
confidence: 75%
“…Las mediciones de los pliegues subcutáneos, el ín-dice de masa corporal y el índice cintura/cadera permiten una aproximación sencilla de la distribución de los diferentes componentes corporales (Garrido-Chamorro et al, 2012;Díaz & Espinoza-Navarro;Moreno, 2012). La composición corporal y el somatotipo, se relaciona directamente con el nivel de condición física y el rendimiento al igual que con la obesidad y las enfermedades cardiovasculares (Flegal et al, 2009;Carter;Lizana Arce et al, 2012).…”
Section: Discussionunclassified